Analisis Value at Risk pada Portofolio Saham PT. Adaro Energy Tbk dan PT. Bukit Asam Tbk Menggunakan Metode Copula Archimedean - Victor Liman; Georgina Maria Tinungki; Anisa Anisa (Hasanuddin University, 2023)
Value at Risk (VaR) is statistical method used in risk analysis in stock investments. Stock returns that are not normally distributed cause the risk calculation to be less precise, so to overcome this, the copula method can be used. Copula is a method based on dependencies between variables. The most commonly known copula family is the Archimedean copula which consists of the Clayton, Frank, and Gumbel copula. VaR is expected to be a feasible method to use, so it is important to perform backtesting. In this research, we use data on the daily closing price of PT. Adaro Energy Tbk and PT. Bukit Asam Tbk May 11, 2020 until June 15, 2022. The best copula based on the smallest Empirical copula value is Frank copula. VaR estimates for the 90%, 95%, and 99% confidence levels respectively were 2.688%, 3.545%, and 5.014%. The higher the confidence level, the VaR value is also higher. Based on backtesting results, VaR with Frank copula method is valid at 90%, 95%, and 99% confidence levels.